(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the applicability of DNA barcode markers for the identification of selected hepatoprotective medicinal plants marketed in Can Tho City, Vietnam. Methods: Five medicinal plant samples, including Phyllanthus urinaria (diệp hạ châu), Curcuma longa (turmeric), Centella asiatica (gotu kola), Glinus oppositifolius (rau đắng), and Senna alata (muồng trâu), were collected in Can Tho City. Total genomic DNA was extracted and amplified by PCR using three DNA barcode markers (ITS, rbcL, and matK), followed by Sanger sequencing. The obtained sequences were compared with reference sequences in the GenBank database using the BLAST tool for species identification. Results: All samples were successfully amplified and sequenced. BLAST analysis showed that the obtained sequences shared 99–100% similarity with their corresponding reference sequences in the GenBank database, enabling accurate species-level identification of all medicinal plant samples. Conclusion: DNA barcoding based on ITS, rbcL, and matK markers combined with Sanger sequencing demonstrated high efficiency in the identification of hepatoprotective medicinal plants. The findings provide preliminary data to support quality control, authentication of plant origin, and the reduction of species misidentification in the medicinal plant market.